2017
DOI: 10.1038/gt.2017.42
|View full text |Cite
|
Sign up to set email alerts
|

CD34+ cells from dental pulp stem cells with a ZFN-mediated and homology-driven repair-mediated locus-specific knock-in of an artificial β-globin gene

Abstract: In humans, mutations in the β-globin gene (HBB) have two important clinical manifestations: β-thalassemia and sickle cell disease. The progress in genome editing and stem cell research may be relevant to the treatment of β-globin-related diseases. In this work, we employed zinc-finger nuclease (ZFN)-mediated gene integration of synthetic β-globin cDNA into HBB loci, thus correcting almost all β-globin mutations. The integration was achieved in both HEK 293 cells and isolated dental pulp stem cell (DPSCs). We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Various studies targeted HBB gene with different gene editing methodologies in various types of cell and cell lines (Antony et al, 2018;Cai et al, 2018;Chattong et al, 2017;Dever et al, 2016;Hoban et al, 2016a;Vakulskas et al, 2018;Wattanapanitch et al, 2018;Ye et al, 2016). However, our study is the first study testing long gRNA including SCD specific mutation and its effects in HBB gene editing.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies targeted HBB gene with different gene editing methodologies in various types of cell and cell lines (Antony et al, 2018;Cai et al, 2018;Chattong et al, 2017;Dever et al, 2016;Hoban et al, 2016a;Vakulskas et al, 2018;Wattanapanitch et al, 2018;Ye et al, 2016). However, our study is the first study testing long gRNA including SCD specific mutation and its effects in HBB gene editing.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies targeted HBB gene with different gene editing methodologies in various types of cell and cell lines (Antony et al, 2018;Cai et al, 2018;Chattong et al, 2017;Dever et al, 2016;Hoban et al, 2016a;Vakulskas et al, 2018;Wattanapanitch et al, 2018;Ye et al, 2016). However, our study is the first study testing long gRNA including SCD specific mutation and its effects in HBB gene editing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the role of SCAPs during root formation is observed in many studies [5]. Interestingly, in vivo studies showed that root development can be halted when cells were isolated from tooth buds at an early stage [6]. Taken together, the easy accessibility and superior properties established them as an attractive choice for tooth and bone tissue engineering.…”
Section: Introductionmentioning
confidence: 99%